The Impact of the Sacred Sites in the Particularity of the City - Rasheed, Khansaa Ghazi; Abdel Hamza, Sarah Munther (Iraqi Journal of Architecture and Planning, 2018)
Abstract The sacred sites considered as explicit spiritual and architectural symbols, enhance the memory of what society holds of history, culture and the nature of his relationship with the sacred, which contribute to enhancing the privacy of the city through what is achieved from the meanings interact with human directly affect the city properties of architectural and urban features on different material and spiritual level. Basically, the research began by searching about the sacred concept in various fields down to discuss studies and proposals that dealwith the holy sites and the content of the types and characteristics and spiritual values, so the research set his field in :( the importance of the holy sites and their effect on the city).obviously, each city hasmany factors affecting on its diverse spiritual and material values which are shows clearly inthe Particularity of the City, so the research went to study the city’s particularity and put the research problem as represented by: (there is a lack of a clear vision in the impact of the holy sites on the particularity of the city), and then move on to see the analyzing ofsome distinguished citieswhich have a lot of sacred sites.Where the search addressed the research problem to the main hypothesis represented as: (influence of the holy sites on the particularity of the city shows through physical dimension). For the purpose of verifying the validity of the assumptions a group of holy sites in the holy city of Najaf that carry spiritual properties were selected and it has been tested by a questionnaire that was distributed to the intentional samples. The research found that the holy sites and have a role in the particularity of the city through all the urban composition and functional properties of values, and revealed a disparate impact of holy sites in local towns than in cities of the world in a way that reinforcing the particularity of each of them.